Phase diagrams, densities and refractive indexes of poly(ethylene oxide) + organic salts + water aqueous two-phase systems: effect of temperature, anion and molar mass - Rengifo, Andrés Felipe Chamorro; Ferreira, Gabriel Max Dias; Ferreira, Guilherme Max Dias; Silva, Maria C. Hespanhol da; Silva, Luis Henrique Mendes da (Fluid Phase Equilibria, 2015)
The application of aqueous two-phase systems (ATPSs) at the industrial level requires systems formed by non-toxic substances to decrease the negative impact on the environment. Organic salts such as sodium citrate, sodium tartrate and sodium succinate have been utilized in order to fulfill this objective. In this work, ATPSs formed by poly(ethylene oxide), PEO, with molar mass 10,000 or 35,000 g mol^−1, organic salts and water, namely PEO10000 + sodium citrate + water, PEO10000 + sodium tartrate + water, PEO10000 + sodium succinate + water and PEO35000 + sodium citrate + water ATPSs at (283.15, 298.15 and 313.15) K have been studied. Effects of temperature, anion and polymer molar mass on the phase diagrams, as well as, the densities and refractive indexes of both phases of the ATPSs were evaluated. The segregation process was endothermic and entropically driven for all ATPSs. The biphasic region on the phase diagrams increased as the molar mass of PEO increased. In addition, the biphasic region also increased in relation to the anions studied: citrate > tartrate > succinate. The consistency of the tie-line data was ascertained by applying the Othmer–Tobias correlation.
Keywords: Aqueous two-phase system; Organic salts; Poly(ethylene oxide); Phase diagram; Liquid–liquid equilibrium